Sucrose-induced anthocyanin accumulation in vegetative tissue of Petunia plants requires anthocyanin regulatory transcription factors. (November 2016) - Ai, Trinh Ngoc; Naing, Aung Htay; Arun, Muthukrishnan; Lim, Sun-Hyung; Kim, Chang Kil
Highlights: The anthocyanin content detected in transgenic plants was higher than that in non-transgenic plants. Increasing sucrose concentration strongly enhanced anthocyanin content in transgenic plants. In addition, sucrose affected plant growth of NT and transgenic plants. Abstract: The effects of three different sucrose concentrations on plant growth and anthocyanin accumulation were examined in non-transgenic (NT) and transgenic (T2 ) specimens of the Petunia hybrida cultivar 'Mirage rose' that carried the anthocyanin regulatory transcription factors B-Peru + mPAP1 or RsMYB1. Anthocyanin accumulation was not observed in NT plants in any treatments, whereas a range of anthocyanin accumulation was observed in transgenic plants. The anthocyanin content detected in transgenic plants expressing the anthocyanin regulatory transcription factors (B-Peru + mPAP1 or RsMYB1) was higher than that in NT plants. In addition, increasing sucrose concentration strongly enhanced anthocyanin content as shown by quantitative real-time polymerase chain reaction (qRT-PCR) analysis, wherein increased concentrations of sucrose enhanced transcript levels of the transcription factors that are responsible for the induction of biosynthetic genes involved in anthocyanin synthesis; this pattern was not observed in NT plants. In addition, sucrose affected plant growth, although the effects were different between NT and transgenic plants. Taken together, the application of sucrose could enhance anthocyanin production in vegetative tissue of transgenic Petunia carrying anthocyanin regulatory transcription factors, and this study provides insights about interactive effects of sucrose and transcription factors in anthocyanin biosynthesis in the transgenic plant.